2007
DOI: 10.1080/03601230701316465
|View full text |Cite
|
Sign up to set email alerts
|

Review of strobilurin fungicide chemicals

Abstract: Strobilurins are natural products isolated and identified from specific fungi. Natural strobilurins were named in the order of their discovery as strobilurin-A followed by strobilurin-B, C, D etc. Their discovery opened the door for new chemistry of synthetic fungicides. Applying Quantitative Structural Activity Relationship (QSAR) on the structures of the natural strobilurins, many pesticide companies were able to discover many synthetic analogues that are more efficacious and more stable fungicides. At prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
207
0
15

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 335 publications
(225 citation statements)
references
References 17 publications
3
207
0
15
Order By: Relevance
“…The molecular targets of the HIF-1 inhibitors identified from our screen remain to be defined. A structure-based patent search revealed that the alkyliminophenylacetate compounds contain the toxophores of the strobilurin fungicides (32,33). Azoxystrobin inhibits electron transfer in the cytochrome bc1 complex of the mitochondrial respiratory chain before cytochrome b, resulting in the preventing cytochrome b reduction and thereby attenuating ROS production (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular targets of the HIF-1 inhibitors identified from our screen remain to be defined. A structure-based patent search revealed that the alkyliminophenylacetate compounds contain the toxophores of the strobilurin fungicides (32,33). Azoxystrobin inhibits electron transfer in the cytochrome bc1 complex of the mitochondrial respiratory chain before cytochrome b, resulting in the preventing cytochrome b reduction and thereby attenuating ROS production (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…They have played a role in the disease management of various agricultural products and are widely used, accounting for over 10% of the fungicide market (Bartlett et al, 2002). The mode of action in fungi is to bind to the quinol oxidation site of cytochrome b in the mitochondrial electron transport chain and thereby block electron transfer, which leads to the inhibition of energy (ATP) production and then the fungi ultimately die (Balba, 2007). Among the strobilurin class, trifloxystrobin (TRF) is a broad-spectrum, widely-used fungicide.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a long term experiment was conducted to evaluate the efficacy of new generation bio-rational fungicide of 'strobilurin derivatives' . Strobilurins (also known as β-methoxyacrylates) or QoI (Quinone outside Inhibitors) fungicides, launched in 1996 are analogues of strobilurin-A [4] originally derived from natural products [5] (Strobilurus tenacellus, a wild mushroom growing in forests). Strobilurins, are now the second largest chemistry group of fungicides, widely used on cereals and, more recently, on soybeans (a market that reached $600 million in 2004).…”
Section: Introductionmentioning
confidence: 99%